2022
DOI: 10.1029/2022wr032481
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Framework for Rapidly Locating Transition Zones: A Comparison of Event‐ and Response‐Based Return Water Levels in the Suwannee River FL

Abstract: Transition zones are stretches of river where extreme water levels can arise through the interaction of multiple drivers such as elevated river discharge, storm surge, and high tide (Bilskie & Hagen, 2018). Transition zones are likely to exist along rivers throughout the world and tend to be most dramatically revealed during catastrophic flood events, such as Hurricane Harvey (2017) where coincident heavy rainfall and surge flooded Houston and the surrounding area (Stephens et al., 2022;Valle-Levinson et al., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…Previous studies have shown model inputs (e.g., gauge measurements, digital elevation models, distributions) pose a significant source of uncertainty on results (Bates et al, 2014;Coveney & Fotheringham, 2011;Saint-Geours et al, 2015;Sampson et al, 2014). There is an increase in studies evaluating current methodologies and their influence on design event estimates (Arns et al, 2013;Jane et al, 2020Jane et al, , 2022Lucey & Gallien, 2022;Sadegh et al, 2018). Arns et al (2013) explores how design events are influenced by detrending methods, utilized sampling, and distribution selection.…”
Section: Variable Pairs Referencesmentioning
confidence: 99%
“…Previous studies have shown model inputs (e.g., gauge measurements, digital elevation models, distributions) pose a significant source of uncertainty on results (Bates et al, 2014;Coveney & Fotheringham, 2011;Saint-Geours et al, 2015;Sampson et al, 2014). There is an increase in studies evaluating current methodologies and their influence on design event estimates (Arns et al, 2013;Jane et al, 2020Jane et al, , 2022Lucey & Gallien, 2022;Sadegh et al, 2018). Arns et al (2013) explores how design events are influenced by detrending methods, utilized sampling, and distribution selection.…”
Section: Variable Pairs Referencesmentioning
confidence: 99%
“…In terms of mean annual river discharge (300 m 3 /s) and drainage area (25,770 km 2 ), it is the second largest river in Florida (Farrell et al., 2005). As the Suwannee river flows to the Gulf of Mexico, it is fed by three major tributaries, the Apalaha, Withlacoochee, and Santa Fe rivers (Jane et al., 2022). At its lower reaches, the river bifurcates into two branches, East and West Pass.…”
Section: Study Areamentioning
confidence: 99%
“…The 100 year flood, based on exceedance probabilities of past, stationary forcing conditions, is the current standard for floodplain management within state and federal agencies in the United States. However, identifying a single event that constitutes a 100 year flood is not straightforward [29][30][31], particularly in the Californian context where some of the most destructive floods, including the 1861-62 flood [32] and the flooding that occurred in early 2023, were not created by a single rainfall event but by a sequence of atmospheric rivers occurring in close succession.…”
Section: Introductionmentioning
confidence: 99%